Distinct Dynamics of Striatal and Prefrontal Neural Activity During Temporal Discrimination - Kim, Jieun; Kim, Dohoung; Jung, Min Whan (Frontiers in Integrative Neuroscience, 2018)
The frontal cortex-basal ganglia circuit plays an important role in interval timing. We examined neuronal discharges in the dorsomedial and dorsolateral striatum in rats performing a temporal categorization task and compared them with previously recorded neuronal activity in the medial prefrontal cortex (mPFC). All three structures conveyed significant temporal information, but striatal neurons seldom showed the prolonged, full-interval spanning ramping activity frequently observed in the mPFC. Instead, the majority fired briefly during sample intervals. Also, the precision of neural time decoding became progressively worse with increasing time duration in the mPFC, but not in the striatum. With the caveat that mPFC and striatal units were recorded from different animals, our results suggest that the striatum and mPFC convey temporal information via distinct neural processes.